PENGARUH KOMPOSISI DAMAR MATA KUCING PADA PEMBUATAN LILIN BATIK TERHADAP KUALITAS PEWARNAAN HASIL PEMBATIKAN - Abdul Malik; Nadia Nadia; Khairunnisa Khairunnisa (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Batik is an Indonesian heritage which has variety of motifs and colors. It has visual and philosophical meaning in every scratch. Wax is used to cover fabric surface so that the pattern can be formed during the coloring process. There are two kinds of wax which are tembokan wax for batik tembokan and klowong wax for batik klowong. Batik klowong has a line and dot motifs and ornaments on the cloth asdecoration. The objective of this study is to determine the composition of opal resin required on wax batik klowong and to know its effect on the finished batik. This study uses qualitative and quantitative methods such as materials measurement, observation by using tools, questionnaire and count the number of voters. The composition of making klowong wax is night wasp, resin, and white paraffin. The independent variable is night wasp with the composition of resin (10 g, 20 g, 30 g, 40 g). Four samples of opal resin were created to test the composition of batik klowong wax on the coloring result. Ten respondents fill the questionnaire as a test to visually see and choose the best samples according to their opinions. The results show that sample D has highest quality and sharpness of color.